Community of peer mentors ©: A new model for peer mentoring in doctoral education - Catherine A. Hansman (Adult Education Research Conference, 2013)
Many issues complicate establishing faculty/student mentoring relationships, including how faculty members and graduate students can engage in mentoring in these challenging times of limited funding for higher education. This roundtable paper briefly examines mentoring models in higher education and proposes a new model, Community of Peer Mentors ©.